On the practical use of weld improvement methods - Nussbaumer, A. (2001)
Many laboratory studies have shown the beneficial effects of weld improvement methods on the fatigue strength of welded details. However, no structural codes systematically include weld improvement methods in detail classification. The purpose of this paper is to discuss the possibilities of using these methods in practice on either new or existing structures. This paper provides the reader with practical rules for designing and computing the fatigue strength of improved welded joints. A computation method based on the concept of effective stress range is introduced to model the effects of peening improvement methods on fatigue strength. For the most popular improvement methods, the fatigue strength of improved details can be deduced from the extensive existing database of full-scale test results. However, for non-classified details, or when fabrication and improvement processes require validation, testing of the improved details is the only method available to guarantee the fatigue strength of a particular detail. In this paper a recent application of validation through testing in the case of longitudinal attachments is described.